LATIHAN ROHANI PEMULA UNTUK PESERTA MUSLIM: STUDI KASUS TIGA PENGALAMAN - Sumarwan, Antonius; Prameswarawati, Yohanna Tungga (Spiritualitas Ignasian: Jurnal Kerohanian dalam Dunia Pendidikan, 2025)
The First Spiritual Exercises is an adaptation of the Spiritual Exercises of St. Ignasius Loyola, designed to make them more accessible to a wider audience. In Indonesia, The First Spiritual Exercises have been introduced as Latihan Rohani Pemula (LRP) and are conducted through online accompaniment, enabling participation from people of diverse backgrounds, including Muslims. This study aims to explore the experiences of Muslim participants in LRP and its impact on their spiritual life and inner well-being. Employing a qualitative approach with a case study design, this research examines the experiences of three Muslim participants who took part in LRP: two active (registered) participants and one passive (unregistered) participant. Data were collected through telephone interviews, written reflections, and triangulation with facilitators and significant others (family members or companions). Descriptive analysis was conducted through processes of data organization, coding, and reduction into key themes. The findings show that despite differences between active and passive participants, both experienced meaningful benefits, including growth in prayer, experiences of God’s love, reconciliation with themselves and others, and more realistic changes in attitudes and behavior. This study affirms that LRP can contribute to the development of interfaith spirituality, support mental well-being, and open spaces for practical dialogue between Islam and Christianity.